Vulnerability and policy relevance to drought in the semi-arid tropics of Asia - A retrospective analysis - Singh, Naveen P.; Bantilan, Cynthia; Byjesh, K. (Elsevier, 2014)
Of all the natural hazards, drought affects the maximum number of people globally causing devastating impacts. It is a reality that drought results in sets of socio-economic impacts starting with crop-yield failure, unemployment, erosion of assets, income decrease, poor nutrition and decreasing risk absorptive capacity, thereby increasing the vulnerability of the community. This paper gives a brief of the existing approaches that focus on vulnerability and impact assessment aid to characterize and identify regions, sectors and communities which are at risk for drought currently and in the future. It also discusses the limitation, constraints and pre-requisites in these approaches and highlights the importance of micro-level information to have a more realistic understanding of impact and vulnerability through illustration, with reference to the recent study conducted by the International Crops Research Institute for the Semi-Arid Tropics (ICRISAT). This exercise will provide a guiding framework for devising action plans to improve adaptive capacity among vulnerable populations.